Religious Moderation in The Industrial Era 4.0: Deradicalization Through The Development of Intellectual Traditions at Fadhlul Fadhlan Islamic Boarding School Semarang - Nurul Azizah; Erry Nurdianzah; Mirza Mahbub Wijaya; Tomi Azami; Anas Rohman (Jurnal Pendidikan Agama Islam, 2023)
Purpose – The Industrial Revolution 4.0, which facilitates open internet access, has presented an era of disruption in human life. The impact is the rapid dissemination of news and information in society. Using religious issues in Indonesia, the radicalism (radical movements) use this situation to spread provocations through social media. This study aims to examine deradicalization efforts through the development of intellectual traditions at the Fadhlul Fadhlan Islamic Boarding School Semarang (Pondok Pesantren Fadhlul Fadhlan Semarang). Design/methods/approach – This research is a qualitative field research with a case study approach. Field data were obtained through observation, documentation, and interview techniques on two groups of resource persons, boarding school caregivers (Kiyai, Bu Nyai) and 20 students. Findings – Deradicalization efforts at the Fadhlul Fadhlan Islamic Boarding School are carried out without any social frictions, namely by developing digitalization of pesantren traditions, such as creating content for yellow book recitation, halaqah, and seminars. These activities can be accessed not only by students but also by the general public through Pesantren's digital media like YouTube and Facebook. Research implications/limitations – This study provides a scientific contribution that has a significant impact on the learning development in Islamic boarding schools in the disruption era. However, some limitations still exist, such as limited research places, namely only conducted in one Islamic boarding school. Therefore, similar research needs to be carried out in other Islamic boarding schools to strengthen or develop deradicalization models in Islamic boarding schools. Originality/value – Digital technology has a significant role in the dynamics of Salaf Islamic boarding schools (pesantren salaf). These findings contribute to the discourse of education in Islamic boarding schools that can adapt to modern educational paradigms. From this discourse, it was found that the integration of Islamic boarding schools with modern technology can be a means of massive deradicalization.